2015
DOI: 10.1016/j.jcrs.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term postoperative outcomes after bilateral congenital cataract surgery in eyes with microphthalmos

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Posterior synechiae were the most frequently observed complication in our study, occurring in 21.4% of 42 microphthalmic eyes and 19.0% of normally developed eyes. In the study by Praveen et al, 37 the incidence of posterior synechiae was 27.8%, whereas Vasavada et al 21 reported a higher incidence of 35.7%. In the present study, one eye in the microphthalmos group developed glaucoma due to pupillary atresia caused by posterior synechiae.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Posterior synechiae were the most frequently observed complication in our study, occurring in 21.4% of 42 microphthalmic eyes and 19.0% of normally developed eyes. In the study by Praveen et al, 37 the incidence of posterior synechiae was 27.8%, whereas Vasavada et al 21 reported a higher incidence of 35.7%. In the present study, one eye in the microphthalmos group developed glaucoma due to pupillary atresia caused by posterior synechiae.…”
Section: Discussionmentioning
confidence: 92%
“…[39][40][41][42][43][44] In the present study, the incidence of VAO was 14.3% in the microphthalmos group, which was similar to that in previous studies on microphthalmos, ranging from 5.2-16.7%. 21,37,45,46 The incidence of postoperative VAO may also vary according to differences in the individual development of pupil and surgical experience and technique among surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Prasad et al, [ 27 ] 5/37 microphthalmos developed glaucoma after surgery. Praveen et al, [ 28 ] showed a rate of glaucoma of 11/37. In the present study, some patients developed intraocular hypertension after surgery, and most of them were improved after conservative drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggested that cataract surgery in children younger than 2 years should include primary IOL implantation, associated with optic capture or bag-in-the-lens IOL implantation techniques to reduce PCO incidence (16). However, when cataract is associated with others ocular conditions as microphthalmia, IOL implantation should be delayed (21). Foldable hydrophobic acrylic is one of most used IOL material, since it remains stable and leads to less severe inflammation and PCO (22).…”
Section: Cataract Diagnosis and Managementmentioning
confidence: 99%